HPV driven squamous cell head and neck cancer of unknown primary is likely to be HPV driven squamous cell oropharyngeal cancer. (August 2020) - Schroeder, Lea; Pring, Miranda; Ingarfield, Kate; Pawlita, Michael; Leary, Sam D.; Thomas, Steve J.; Waylen, Andrea; Waterboer, Tim; Ness, Andy R.
Highlights: Up to 5% of the head and neck cancers are carcinoma of unknown primary (CUP). A substantial proportion of people with CUP have HPV driven tumours. Prospective studies have not compared with CUP and oropharyngeal cancer (OPC). Our data confirm that HPV driven CUP is likely to be HPV driven OPC. Methods of locating occult OPC could improve CUP treatment and early OPC detection. Abstract: Objectives: To compare risk factors and survival in people with oropharyngeal cancer (OPC) and cancer unknown primary (CUP). Materials and methods: We recruited 5511 people with head and neck cancer between 2011 and 2014. We collected data on age, gender, smoking, sexual behaviour, treatment intent, stage, co-morbidity, p16 protein overexpression and biological samples. We assessed human papillomavirus (HPV) status using serological response and p16 immunohistochemistry. We followed up participants to identify those who had died. We used Cox proportional hazards regression models to estimate survival and adjust for confounders. Results: Of the 4843 people with squamous cell cancer 196 had CUP – a prevalence of 4.0% (95% CI 3.5% to 4.6%). Of those people with OPC and CUP 69% (1150/1668) and 60% (106/178) respectively had HPV driven tumours. People with HPV driven tumours were likely to be younger, male, non-smokers, with higher stage disease, a history of oral sex and less co-morbidity. People with HPV negative CUP and HPV driven CUP had the survival of people with a stage II/III HPV negative OPC and a stage I/II HPV driven OPC respectively. The adjusted hazard ratio for HPV driven OPC and CUP compared with HPV negative OPC and CUP was 0.46 (95% CI 0.35 to 0.59) and 0.34 (95% CI 0.14 to 0.82) respectively. Conclusion: HPV driven CUP is likely to be HPV driven OPC. Identifying effective methods of detecting occult OPC could improve CUP management and allow the detection of early lesions in high risk groups.